2015
DOI: 10.2139/ssrn.2625642
|View full text |Cite
|
Sign up to set email alerts
|

Are British Muslims Alienated from Mainstream Politics by Islamophobia And British Foreign Policy?

Abstract: This paper uses the 2010 Ethnic Minority British Election Study to look at the political attitudes of Muslims in Britain. It tests the relationship between political alienation and political participation on the one hand, and Islamophobia and disapproval of British military involvement in Afghanistan on the other. The principal findings are that perceptions of Islamophobia are linked to greater political alienation, to a greater likelihood of non-electoral participation and to a lower likelihood of voting amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
1
4
0
3
Order By: Relevance
“…Tidligere studier, der undersøger effekterne af et politisk klima praeget af modvilje mod indvandring og kulturel diversitet, har primaert fokuseret på, hvordan dette klima påvirker politisk deltagelse blandt etniske minoriteter. Nogle studier finder, at en sådan kontekst fremmer deltagelse (Pantoja, Ramirez og Segura, 2001;Ramakrishnan og Espenshade, 2001;Pérez, 2015b;Cinalli og Giugni, 2011, mens andre finder, at det svaekker deltagelse (Martin, 2016;Sanders et al, 2014;Just og Anderson, 2014), eller at det fremmer deltagelse, indtil konteksten bliver saerlig fjendtlig (Tyrberg, 2019). Vi undersøger effekten af et fjendtligt politisk klima på politisk effektivitetsfølelse og politisk tillid, hvilket faerre studier tidligere har gjort.…”
Section: Eksisterende Forskningunclassified
See 1 more Smart Citation
“…Tidligere studier, der undersøger effekterne af et politisk klima praeget af modvilje mod indvandring og kulturel diversitet, har primaert fokuseret på, hvordan dette klima påvirker politisk deltagelse blandt etniske minoriteter. Nogle studier finder, at en sådan kontekst fremmer deltagelse (Pantoja, Ramirez og Segura, 2001;Ramakrishnan og Espenshade, 2001;Pérez, 2015b;Cinalli og Giugni, 2011, mens andre finder, at det svaekker deltagelse (Martin, 2016;Sanders et al, 2014;Just og Anderson, 2014), eller at det fremmer deltagelse, indtil konteksten bliver saerlig fjendtlig (Tyrberg, 2019). Vi undersøger effekten af et fjendtligt politisk klima på politisk effektivitetsfølelse og politisk tillid, hvilket faerre studier tidligere har gjort.…”
Section: Eksisterende Forskningunclassified
“…Disse viser overordnet en negativ effekt. Ingen tager dog udgangspunkt i indvandrere og efterkommeres egne opfattelser af det politiske klima (se dog Martin, 2016og Sanders et al, 2014 omkring opfattet gruppediskrimination). I stedet anvendes forskellige objektive mål, som alle har deres berettigelse.…”
unclassified
“…One of the few quantitative studies of British Muslims' political alienation concluded that British Muslims are equally, and on some indicators even less alienated than the non-Muslim population. 46 The measure of alienation used in the study consisted of indicators of political attitudes and behaviour such as voting, trust in politicians, political efficacy, or satisfaction with democracy, and it was based on data from 2010. On these indicators, the non-alienated part of the British Muslim population was estimated to be between 60 and 70 % at the time.…”
Section: Negative Attitude To Counter-terrorism and Counter-extremism Policiesmentioning
confidence: 99%
“…It is even more difficult to make judgements about the level of actual or potential engagement in counter-terrorism activities among Muslims. In fact, the few existing quantitative studies indicate that trust in the government 14 and the police 15 is higher among British Muslims than among the majority population, the level of "political alienation" is comparable or lower among Muslims than in the rest of society 16 and Muslims show very high levels of readiness to take action against Islamist extremism. 17 The objective of this article is to reassess and nuance the widespread assumption about Muslim alienation and Muslims' willingness to engage in counter-terrorism.…”
Section: Introductionmentioning
confidence: 99%
“…discrimination has become highly salient to Muslims (Martin 2017). In addition, it is often argued that the top-down counter-extremism approach alienates Muslim communities (e.g., Abbas and Awan 2015;Bonino 2013;O'Toole et al 2016;Saeed and Johnson 2016).…”
mentioning
confidence: 99%